Surface Wave and Roller Dissipation Observed With Shore‐Based Doppler Marine Radar. Issue 8 (24th August 2022) - Streßer, Michael; Horstmann, Jochen; Baschek, Burkard
Abstract: Surface wave energy and dissipation are observed across the surf zone. Utilizing the concept of surface rollers, a new scaling is introduced to obtain the energy flux and dissipation related to rollers from Doppler velocities measured by a shore‐based X‐band marine radar. The dissipation of wave energy and hence the transformation of the incoming wave height (or energy) is derived using the coupled wave and roller energy balance equations. Results are compared to in‐situ wave measurements obtained from a wave rider buoy and two bottom mounted pressure wave gauges. A good performance in reproducing the significant wave height is found yielding an overall root‐mean‐square error of 0.22 m and a bias of −0.12 m. This is comparable to the skill of numerical wave models. In contrast to wave models, however, the radar observations of the wave and roller energy flux and dissipation neither require knowledge of the bathymetry nor the incident wave height. Along a 1.5 km long cross‐shore transect on a double‐barred, sandy beach in the southern North Sea, the highest dissipation rates are observed at the inner bar over a relatively short distance of less than 100 m. During the peak of a medium‐severe storm event with significant wave heights over 3 m, about 50% of the incident wave energy flux is dissipated at the outer bar. Plain Language Summary: Ocean waves are carrying a large amount of mechanical energy which they have gained from the wind blowing over the ocean surface. At the coast this energy supply generates strong water motions, creates forces on coastal structures, moves sand, and can cause coastal erosion. It is therefore important to know when, where, and to what extent wave energy is reduced under different environmental conditions. The majority of the energy is removed by wave breaking. However, this process is still not completely understood which is partly due to fact that it is difficult to observe. This is particularly the case during storm conditions when it is very complicated to install and recover measurement equipment in the ocean. The present work describes a methodology to obtain such measurements using a special radar device which is installed at the beach; hence, it is not being impacted by harsh wave conditions. This approach will enable scientists to perform long‐term monitoring of wave breaking thus opening new opportunities to study beach processes and coastal changes. Key Points: high‐resolution observations of surface wave and roller dissipation as well as the transformation of wave height across the surf zone the concept of surface rollers is applied to shore‐based X‐band Doppler radar data in storm conditions, 50% of the wave energy is dissipated at a submerged outer sandbar, but strongest dissipation occurs further inshore